Multi-scale comparative transcriptome analysis reveals key genes and metabolic reprogramming processes associated with oil palm fruit abscission - Fooyontphanich, Kim; Morcillo, Fabienne; Joët, Thierry; Dussert, Stéphane; Serret, Julien; Collin, Myriam; Amblard, Philippe; Tangphatsornruang, Sithichoke; Roongsattham, Peerapat; Jantasuriyarat, Chatchawan; Verdeil, Jean-Luc; Tranbarger, Timothy J. (BMC plant biology, 2021)
Fruit abscission depends on cell separation that occurs within specialized cell layers that constitute an abscission zone (AZ). To determine the mechanisms of fleshy fruit abscission of the monocot oil palm (Elaeis guineensis Jacq.) compared with other abscission systems, we performed multi-scale comparative transcriptome analyses on fruit targeting the developing primary AZ and adjacent tissues. Combining between-tissue developmental comparisons with exogenous ethylene treatments, and naturally occurring abscission in the field, RNAseq analysis revealed a robust core set of 168 genes with differentially regulated expression, spatially associated with the ripe fruit AZ, and temporally restricted to the abscission timing. The expression of a set of candidate genes was validated by qRT-PCR in the fruit AZ of a natural oil palm variant with blocked fruit abscission, which provides evidence for their functions during abscission. Our results substantiate the conservation of gene function between dicot dry fruit dehiscence and monocot fleshy fruit abscission. The study also revealed major metabolic transitions occur in the AZ during abscission, including key senescence marker genes and transcriptional regulators, in addition to genes involved in nutrient recycling and reallocation, alternative routes for energy supply and adaptation to oxidative stress. The study provides the first reference transcriptome of a monocot fleshy fruit abscission zone and provides insight into the mechanisms underlying abscission by identifying key genes with functional roles and processes, including metabolic transitions, cell wall modifications, signalling, stress adaptations and transcriptional regulation, that occur during ripe fruit abscission of the monocot oil palm. The transcriptome data comprises an original reference and resource useful towards understanding the evolutionary basis of this fundamental plant process.